Elastic and Thermoelastic Effects on Thermal Water Convection in Fracture Zones. Issue 2 (3rd February 2021) - Patterson, James W.; Driesner, Thomas
Abstract: Natural groundwater convection in fractures is an important mechanism of mass and heat transfer in the subsurface, locally altering temperature by several tens of degrees. The thermoelastic stresses resulting from these thermal anomalies induce thermal strains, which in turn alter the transmissivity (permeability times thickness) of the fracture and, therefore, the convective flow within. We investigate the effect of thermal strains on fracture convection patterns using a three‐dimensional thermo‐hydraulic‐mechanical numerical model, implementing the Barton‐Bandis relationship between fracture transmissivity and effective normal stress, which results in a downward‐narrowing of the fractures. When thermoelasticity is not taken into account, convection forms narrow upflow zones and wide downflow zones. Decreasing fracture stiffness results in similar upflow/downflow patterns, but restricted to the shallow portions of the fracture, creating relatively minor thermal changes. When thermo‐elasticity is included in the model, thermal strains induced by cool downflow zones create narrow high‐transmissivity channels within the fracture, allowing convective flow to reach greater depths and significantly reducing the geothermal gradient near the fracture. Fracture stiffness is a key parameter in determining convection depth and thermal perturbation strength for a given set of host rock mechanical properties. When fracture stiffness is below some threshold, subsequent contractive thermoelastic strains were found to induce tensile failure of the host rock below the fracture, propagating and deepening the fracture into the host rock. This observation provides support to the previously proposed concept of convective downward migration. Key Points: Natural convection of fluid within a fracture zone with a downward‐tapering transmissivity profile is confined to narrow depths Thermo‐mechanical strains induced by fracture convection create high‐transmissivity downflow channels and increase the depth of convection The thermal strain on the host rock may be large enough to propagate and deepen the initial fracture zone